The relationship between family support with self-concept in patients with post mastectomy - Nurhidayati, Titik; Firdaus, Achmad Dafir; Harningtyas, Sismala (Palembang MediRose Publisher, 2023)
Background: Uncontrolled cancer conditions will cause several impacts, both physiological impacts, as well as psychological impacts such as maladaptive self-concepts. Objective: To determine the relationship between family support and self-concept in post-mastectomy patients. Methods: The variables measured in this study were family support and self-concept. The sample was taken using a purposive sampling technique, namely selecting existing respondents with inclusion and exclusion criteria. In this study, the researcher used an observational analytic research design with a cross sectional approach with a sample of 30 respondents. The measuring instrument used was a questionnaire that was measured using a questionnaire that had been compiled and validated by Nurwulan for family support, while the self-concept questionnaire was adapted from Hartoyo’s theory. Test data analysis using Spearman Rho with ?=0.05. Results: The results showed that most of the patients received high family support as many as 17 people (56.7%). On family support, most of the respondents have a high self-concept as many as 21 people (70%). The results also show that there is a relationship between family support and the patient’s self-concept. with a p-value=0.001 (p<0.05) and r=0.57. Conclusions: Based on the results of this study, it is recommended from nurses in the treatment room, to improve the quality of service and provide support to patients.